Analysis of the main legal acts that regulate language relations in Ukraine - Bigari , Maryna (Theory and Practice of Public Administration, 2019)
In many countries around the world, issues of the protection of the mother language are taken in attention strenghtly, enshrining at the legislative level both the status of the state language and the rules of its use. At the same time enough attention is paid to the language issue not only in the countries that have recently gained their independence, but also in countries where statehood has lasted for centuries. According to language means a lot in forming official, oral, written, informational messages, statements, appeals, etc., language can be called one of the important objects of legal relations between citizens, institutions and authorities. As usual, the legal regime of the state (official) language is guarded in the basic law of the state - in its constitution. In some countries, the legal regime of the state language is not enshrined in current law, but it exists de facto and recognized as custom (for example, in the US, Denmark, the United Kingdom, Norway, Sweden, etc.). Article 10 of the Constitution of Ukraine designates that the official language is Ukrainian language. The analysis of the documents, which became the legal basis for the implementation of the state language policy, makes it possible to conclude that the legal framework in Ukraine generally corresponds to the norms of world practice and contains sufficient tools for its implementation. But the question remains of psychological not perception, resistance to these changes by a separate part of the population, which requires a more systematic approach in the application of the mentioned organizational and legal mechanisms, taking into attention the characteristics of generations. In addition, a profound ways of the current linguistic situation in Ukraine is lacking to develop directions for state language policy. It is not enough to declare the state status of the Ukrainian language for its full validation in all spheres of public life. Mechanisms for implementation of legal documents need to be created.